2016
DOI: 10.1021/acs.nanolett.6b00221
|View full text |Cite
|
Sign up to set email alerts
|

Oleic Acid-Induced Atomic Alignment of ZnS Polyhedral Nanocrystals

Abstract: Ordered two-dimensional (2D) superstructures of colloidal nanocrystals (NCs) can be tailored by the size, shape, composition, and surface chemistry of the NC building blocks, which can give directionality to the resulting superstructure geometry. The exact formation mechanism of 2D NC superstructures is however not yet fully understood. Here, we show that oleic acid (OA) ligands induce atomic alignment of wurtzite ZnS bifrustum-shaped NCs. We find that in the presence of OA ligands the {002} facets of the ZnS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 33 publications
3
38
1
Order By: Relevance
“…The free surfactants in nanoparticle solutions have been largely ignored in most previous studies on self‐assembly, and researchers have just begun to realize their importance . For example, Donega and co‐workers recently reported that the addition of oleic acid for the self‐assembly of nanoparticles at the bulk water/oil interface leads to the atomic‐level alignment of nanoparticles . The work presented here highlights the importance of surfactants in controlling the morphology of colloidal interfacial assembly of nanoparticles.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The free surfactants in nanoparticle solutions have been largely ignored in most previous studies on self‐assembly, and researchers have just begun to realize their importance . For example, Donega and co‐workers recently reported that the addition of oleic acid for the self‐assembly of nanoparticles at the bulk water/oil interface leads to the atomic‐level alignment of nanoparticles . The work presented here highlights the importance of surfactants in controlling the morphology of colloidal interfacial assembly of nanoparticles.…”
Section: Discussionmentioning
confidence: 86%
“…Without extra surfactants in the oil phase, solid assemblies were formed instead of hollow structures, indicating that the surfactant in the oil phase is critical in hindering the shrinkage of nanoparticle membranes formed at the oil/water interface and in promoting the inflow of water through the nanoparticle membranes. The free surfactants in nanoparticle solutions have been largely ignored in most previous studies on self‐assembly, and researchers have just begun to realize their importance . For example, Donega and co‐workers recently reported that the addition of oleic acid for the self‐assembly of nanoparticles at the bulk water/oil interface leads to the atomic‐level alignment of nanoparticles .…”
Section: Discussionmentioning
confidence: 99%
“…Another very efficient analytical tool for characterization of self‐assembled mesocrystalline materials is high‐resolution synchrotron‐based small/wide‐angle X‐ray scattering (SAXS/WAXS) (including in situ time‐resolved grazing incidence small‐angle X‐ray scattering and grazing incidence wide‐angle X‐ray scattering) . These techniques are developing very fast within the last years and are allowing to determine the packing arrangement and orientational order of nanoparticles not only within solid mesocrystals but also to track in situ their structural evolution during the self‐assembly process …”
Section: Introductionmentioning
confidence: 99%
“…The geometry and properties of these superstructures can be tailored by the size, shape, composition and surface chemistry of the NC or hetero-NC building blocks [129138]. In particular, surface ligands have been shown to have a dramatic impact on the directionality of the self-organization process [135, 139143], leading in some cases to atomically aligned NC superlattices [135, 139, 143]. NC thin-films and superlattices hold promise for a variety of optoelectronic devices, such as light emitting devices, solar cells, photodetectors, and field-effect transistors [129, 130], since they may give rise to a number of novel properties dominated by collective interactions such as energy transfer, charge carrier transfer and migration, and inter-NC electronic coupling.…”
Section: Excitons In Semiconductor Nanocrystalsmentioning
confidence: 99%